2008
DOI: 10.1186/1751-0147-50-50
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods inquiry: How dairy farmers perceive the value(s) of their involvement in an intensive dairy herd health management program

Abstract: Background: Research has been scarce when it comes to the motivational and behavioral sides of farmers' expectations related to dairy herd health management programs. The objectives of this study were to explore farmers' expectations related to participation in a health management program by: 1) identifying important ambitions, goals and subjective well-being among farmers, 2) submitting those data to a quantitative analysis thereby characterizing perspective(s) of value added by health management programs amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 23 publications
6
63
0
Order By: Relevance
“…After I started doing this, it seems that the calves come much better" (Man,65). This supports other studies that have also shown technical assistance can influence farmers' perceptions and attitudes and promote positive change (KRISTENSEN & ENEVOLDSEN, 2008;VAARST & SØRENSEN, 2009;CARDOSO et al, 2016b).…”
Section: ----------------------------------------------% Of Total Farsupporting
confidence: 89%
“…After I started doing this, it seems that the calves come much better" (Man,65). This supports other studies that have also shown technical assistance can influence farmers' perceptions and attitudes and promote positive change (KRISTENSEN & ENEVOLDSEN, 2008;VAARST & SØRENSEN, 2009;CARDOSO et al, 2016b).…”
Section: ----------------------------------------------% Of Total Farsupporting
confidence: 89%
“…Previous research has shown that the relationship farmers have with their veterinarian is a significant predictor for participation in VHHM (Derks et al, 2013). Also, veterinarians are not always aware of the goals the farmer wants to reach (Kristensen and Enevoldsen, 2008;Derks et al, 2012b;Hall and Wapenaar, 2012), although knowledge of the farmer's goals is important for compliance to veterinary advice (Sorge et al, 2010). Finally, farmers can be hard to reach with preventive advice and sometimes need a more tailor-made approach (Jansen et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…Work from Scandinavia, utilising the Q methodology (Dziopa and Ahern, 2011), evaluated how dairy farmers perceived the value of involvement in health management programmes (Kristensen and Enevoldsen, 2008). That study challenged the belief that farmer's motivation was predominantly financial, as farmers identified teamwork, animal welfare and knowledge dissemination as their highest priorities.…”
Section: Economics Of Involvement In Incalfmentioning
confidence: 99%